The Contribution of Collaborative Online International Learning (COIL) to Career-Relevant Learning - Joanne Marsh, Michelle Mayer (2026)
This report draws on two interconnected studies examining the contribution of Collaborative Online International Learning (COIL) to career-relevant learning, intercultural competence, and global professional readiness within higher education. The first and larger study was conducted within the iKudu project, co-funded by the Erasmus+ programme of the European Union[1], involving 10 universities across South Africa and Europe. Between 2019 and 2024, more than 3,000 students participated in 65 COIL exchanges across multiple disciplinary and institutional contexts. The iKudu project explored how COIL could contribute to internationalised and decolonised curriculum practices through digitally mediated collaboration and knowledge pluralisation within the broader context of curriculum transformation and comprehensive internationalisation.The second and smaller follow-on study, COILing Careers through iKudu, extended this work by examining how participation in COIL contributed to students’ transversal skill development for employability, further study, and active citizenship. In this context, ‘Careers’ refers to employment and /or study opportunities undertaken during a person's life and with opportunities for progress. Transversal skills refer to capabilities applicable across diverse professional and social contexts, including communication, collaboration, organisation, adaptability, and reflexivity.The study adopted a two-stage multi-method design. Stage 1 analysed open-ended survey responses from 93 students who participated in iKudu COIL exchanges across partner institutions. Stage 2 utilised Story Circles methodology to deepen and contextualise these findings through participant-led narrative reflection. The analysis examined not only how students experienced COIL across different institutional and disciplinary settings, but also how learning developed through interaction, collaboration, reflection, and engagement across difference.The findings indicate that COIL contributes not only to intercultural awareness, but also to communication, coordination, reflexivity, ethical collaboration, language development, and forms of professional readiness associated with globally networked and digitally mediated work environments. At the same time, the study demonstrates that these outcomes vary across contexts and disciplines and are shaped by factors such as task design, modes of collaboration, facilitation, and opportunities for participation. The report contributes to current debates by examining the mechanisms through which COIL learning develops whilst positioning COIL not only as an internationalisation activity, but also as a site of career-relevant and reflective global learning.